PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SUGITY CREATIVES - Afdillah Septian Djati; Muhammad Ramdhan; Muhammad Ridwan (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2020)
This study explores the influence of discipline and work motivation on employee performance at PT Sugity Creatives, addressing a gap in understanding how internal factors specifically affect performance within this company. The research objective is to quantitatively assess the contributions of these variables to employee effectiveness. Employing a descriptive approach with a quantitative methodology, the study encompasses the entire company population of 41 employees using a saturated sampling technique. Multiple linear regression analysis was applied to evaluate the data. The findings confirm significant positive effects: discipline exhibits a notable influence on performance with a t-value of 7.972, exceeding the t-table value of 2.024 and a significance level of 0.000. Similarly, work motivation impacts performance with a t-value of 5.983. Collectively, discipline and motivation significantly enhance performance, evidenced by an F-value of 31.193. These results underscore the critical role of managerial strategies in fostering workplace discipline and motivation to boost employee output. Enhancing these factors could lead to more effective personnel management and improved operational outcomes at PT Sugity Creatives